2010
DOI: 10.1007/s11258-010-9839-1
|View full text |Cite
|
Sign up to set email alerts
|

Tree-shrub associations in grazed woodlands: first rodents, then cattle?

Abstract: Spatial associations of tree saplings with spiny or toxic plants in grazed woodlands are generally explained by associational resistance, i.e., protection against grazing via a well-defended neighbor. In this study, we tested whether directed seed dispersal and post-dispersal seed removal by wood mice are additional explanations for the observed spatial association between thorny shrubs and trees, hence before associational resistance. We performed three studies in grazed woodlands in the Netherlands to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…We also found that the CU proportion was significantly lower than CG when checked at 30 days and the next spring, although initially higher in CU than in CG after 5 days. Previous studies have shown that not only dispersal but also removal of seeds is higher under dense vegetation such as shrubs (Iida 2006;Pérez-Ramos and Marañón 2008;Smit et al 2006, Smit andVerwijmeren 2011), which is again mostly attributed to reduced predation risk (Manson and Stiles 1998). Our results indirectly have demonstrated that cache dynamics were lower in gaps than in the understory, which was beneficial to seeds of light-demanding species.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…We also found that the CU proportion was significantly lower than CG when checked at 30 days and the next spring, although initially higher in CU than in CG after 5 days. Previous studies have shown that not only dispersal but also removal of seeds is higher under dense vegetation such as shrubs (Iida 2006;Pérez-Ramos and Marañón 2008;Smit et al 2006, Smit andVerwijmeren 2011), which is again mostly attributed to reduced predation risk (Manson and Stiles 1998). Our results indirectly have demonstrated that cache dynamics were lower in gaps than in the understory, which was beneficial to seeds of light-demanding species.…”
Section: Discussionsupporting
confidence: 61%
“…Ample evidence suggests that the predation risk may affect the seed-hoarding behavior of rodents (Li and Zhang 2003;Lu and Zhang 2004) and subsequent seedling recruitment (Duncan and Chapman 1999;Li and Zhang 2003). Thus, studies of the seed dispersal patterns in and around open woodlands are important for evaluating the role of seed dispersal by small rodents during the natural regeneration of woody plants (Scheper and Smit 2011;Smit and Verwijmeren 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, large sapling abundance in Retama formations was much more responsive to small sapling abundance compared to that of Cistus formations (Table ), suggesting a cumulative effect under Retama . Smit & Verwijmeren () reported similar results in a grazed wood–pasture system in presence of blackthorn, arguing that a cumulative grazing effect can lead to a strong spatial association between saplings and shrubs over time. The associational resistance theory states that unpalatable species (spiny or toxic) can facilitates palatable species by protecting against herbivores (Olff et al.…”
Section: Discussionmentioning
confidence: 72%
“…Seedling emergence beyond the canopy edge tended to be higher under shrubs than in open spaces. This result suggests an active dispersal of acorns toward shrubs, rather than a passive dispersal, which is common under tree canopies (Smit & Verwijmeren ). In the study area, holm oak mostly relies on rodents for the dispersal of acorns in open woodlands (Muñoz et al.…”
Section: Discussionmentioning
confidence: 89%
“…Numerous biotic and abiotic factors, e.g., predation, habitat, and season, may affect the seed hoarding behavior of rodents (Li and Zhang 2003;Lu and Zhang 2004;Lai et al 2013), and subsequent seedling recruitment (Duncan and Chapman 1999;Li and Zhang 2003;Scheper and Smit 2011;Smit and Verwijmeren 2011;Yu et al 2013a). In particular, the substrate upon which an animal feeds strongly influences foraging behavior (Kotler et al 2001).…”
Section: Introductionmentioning
confidence: 99%